Forging Strategic Partnerships Between Libraries, Collectors and Young Writers - Boluwatife Agbelusi (15408297) (2025)
Libraries are evolving into cultural hubs, fostering knowledge and creativity through strategic partnerships. The Museum of Islamic Art (MIA) Library exemplifies this by collaborating with Rashid Al Muraikhi – a Qatari collector – to display books, figurines and religious and cultural artifacts, including rare Qur’ans and models of the Kaaba. The MIA Library also partners with Qatar Writes and Qatar Reads, hosting writing competitions and showcasing young authors' works. A joint exhibition with Qatar National Library at the MIA Park highlighted Qatar’s cultural heritage. These partnerships enhance learning, engagement and cultural exchange, ensuring libraries remain vibrant and relevant in a digital age. Other Information Poster was presented at: Libraries Thriving Together in an Open Ecosystem https://www.qnl.qa/en/libraries-lead-forum-2025 License: https://creativecommons.org/licenses/by/4.0/ Conference information: Libraries Lead Forum 2025 https://www.qnl.qa/en/libraries-lead-forum-2025/agenda